Mycobacterium tuberculosis nucleoside diphosphate kinase shows interaction with putative ATP binding cassette (ABC) transporter, Rv1273c. Issue 4 (3rd March 2020) - Gupta, Smita; Shukla, Harish; Kumar, Arun; Shukla, Rohit; Kumari, Richa; Tripathi, Timir; Singh, Rakesh K.; Anupurba, Shampa
Abstract: Protein–protein interactions are crucial for all biological processes. Compiling this network provides many new insights into protein function and gives directions for the development of new drugs targeted to the pathogen. Mycobacterium tuberculosis Nucleoside diphosphate kinase (Mtb Ndk) has been reported to promote survival of mycobacterium within the macrophage and contribute significantly to mycobacterium virulence. Hence, the present study was aimed to identify and characterize the interacting partner for Ndk. The in vitro experiments, pull down and far western blotting have demonstrated that Mtb Ndk interacts with Rv1273c, a probable drug ABC transporter ATP-binding protein annotated to export drugs across the membrane. This observation was further confirmed by molecular docking and dynamic simulations studies. The homology model of Rv1273c was constructed and docked with Mtb Ndk for protein–protein interaction analysis. The critical residues involved at interface of Rv1273c–Ndk interaction were identified. MDS and Principal Component analysis carried out for conformational feasibility and stability concluded that the complex between the two proteins is more stable as compared to apo proteins. Our findings would be expected to improve the dissection of protein–protein interaction network and significantly advance our understanding of tuberculosis infection. Communicated by Ramaswamy H. Sarma